RESOURCE DYNAMICS: INDIA’S DEMAND AND JORDAN’S EXPORTS - Al-Azzam, Muhammad Ali; Al-Sharabati, Abdullah Sameer (International Journal of Allied Research in Economics (IJARE), 2023)
This paper examines the trade relations between India and Jordan from 1947 to 1976. The paper begins by providing an overview of the history of Indo-Jordan relations, followed by a discussion of the trade agreements signed between the two countries during this period. The paper then analyzes the trends in trade between India and Jordan, and identifies the factors that have influenced these trends. The paper concludes by discussing the prospects for future trade between the two countries